(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Urethro cutaneous fistula( U-C fistula) is the most common complication of hypospadias surgery. It frequently needs separate surgeries for closure, which bring a great deal of physical and mental agony and monetary involvement of the patient and his family. Many efforts have been invented to prevent the u-c fistula with various degree of success. We would like to see the outcome of Preputial Dartos Reinforced Snodgrass Tubularized Incised Plate Urethroplasties in Distal Hypospadias to Prevent Urethrocutaneous Fistula. This interventional study was performed to see the outcome of preputial dartos reinforced Snodgrass tubularized incised plate urethroplasties in distal hypospadias specially urethrocutaneous fistula prevention. For this purpose 40 patients were selected having distal hypospadias age ranging from 6 months to 11 years admitted in the Department of Pediatric Surgery, Mymensingh Medical College & Hospital during the period of January 2010 to March 2011. Out of 40 patients, 20 were in group-A (preputial dartos flap) and another 20 were included in group - B (without flap). All this patients were followed by perioperative and postoperative care. Few patients developed postoperative pyrexia, wound infection, stent blockage which were treated accordingly leaving minimum morbidity. Both groups of patients were followed up for 3 months after surgery. Present study is probably a better technique to prevent fistulaassociated morbidities in distal Snodgrass TIP urethroplasties. J. Paediatr. Surg. Bangladesh 3(1): 12-17, 2012 (January)